Effect of pre-partum supplementation with calcium chloride on the serum concentration of minerals and productive aspects in Carora cows - Villarreal, Villany (2019)
The aim of this study was to evaluate the effect of pre-partum supplementation with an anionic diet on serum mineral concentrations during the peripartum, occurrence of subclinical hypocalcaemia, retention of foetal membranes and milk production in the first 100 days postpartum. A completely randomized design was used, with 24 Carora cows distributed in two groups: one group supplemented with 100 g of calcium chloride/cow/day between 21 days before the probable date of calving and the day of calving with a BCAD of 9.6 mEq/100 g of MS, and a non-supplemented group. The urinary pH was determined twice a week between day -21 and day 1 of parturition. Serum calcium, phosphorus and magnesium concentrations were determined on days -21, -14, 1, 15 and 30 of calving. Subclinical hypocalcaemia was determined if the serum calcium values were lower than 7.5 mg/dl on days 1 and 15 postpartum. Milk production was determined by monthly weighing records. A decrease in urinary pH was found on days -14, -7 and 1 in the supplemented group (p<0.01). Supplementation with 100 g/cow/day of calcium chloride in the pre-partum increased serum concentrations of magnesium and phosphorus, but serum calcium levels remained like those in the non-supplemented group. Calcium chloride supplementation in the pre-partum did not improve Ca2+ homeostasis or prevent the occurrence of metabolic diseases such as hypocalcaemia and retention of foetal membranes in the postpartum, nor did it increase milk production.